Anaplastic Large Cell Lymphoma, ALK-Negative: A Rare Case with Histopathological and Immunohistochemical Features - Bakri, Bilal Ramez; Baldavira, Camila Machado; Pirani, William Marques; Ab’Saber, Alexandre; Capelozzi, Vera Luiza (Brazilian Journal of Case Reports, 2025)
We report a case of anaplastic large cell lymphoma (ALCL), ALK-negative, diagnosed in a 27-year-old patient presenting with diffuse lymphadenopathy and constitutional symptoms. Histopathological examination revealed sheets of large pleomorphic lymphoid cells, and immunohistochemistry demonstrated CD30 positivity with ALK negativity. This case highlights the diagnostic and therapeutic challenges associated with this rare subtype of T-cell lymphoma and contributes to the growing body of literature on ALCL ALK-negative.